Bajorų pavadinimai – lietuvių pavardžių šaltinis - Čirūnaitė, Jūratė (Baltistica, 2002)
Noble family names as a source of Lithuanian surnames1. Inthe middle of 16th century the names of Lithuanian noble families were used as names of individual nobles, but there were no surnames.2. At the end of 17th century the names of Lithuanian noble family names became surnames. A noble family name could be transformed into a personal name directly or indirectly: an additional suffix might be added, a suffix might be dropped or a suffix might be changed.3. Most surnames which were derived from noble family names at the end of 17th century have survived until the present time.
Keywords: onomastika; pavardės